Process of updating of the regulatory base in construction - O. A. Gorelova (Вестник университета)
An assessment of the state pricing policy in matters ofpricing the construction industry has been given. The estimated regulatory framework and the level of its validity, which is necessary for determining the price of construction products, have been characterized. The state information system of estimated standards, necessary for the formation of a market pricing system in construction, has been considered. The necessity of implementing the reform of construction pricing, which will help to create conditions for the further development of the industry at a new level of reliability and quality of determining reasonable construction prices, has been shown.